High Prevalence of Human Papillomavirus Infection among Brazilian Pregnant Women with and without Human Immunodeficiency Virus Type 1 - Emilia Moreira Jalil; Geraldo Duarte; Patrícia El Beitune; Renata Toscano Simões; Patrícia Pereira dos Santos Melli; Silvana Maria Quintana (Hindawi Limited, 2009)
Objective. To estimate HPV prevalence among pregnant women from Ribeirão Preto, Brazil, and the possible influence of HIV-1 infection on this prevalence. Methods. A cross-sectional study with 44 HIV-positive and 53 HIV-negative pregnant women was conducted. Cervicovaginal specimens were obtained from all women during gynecologic exam. HPV DNA, low and high risk HPV types, was detected using conventional PCR. Statistical analysis used Student's t-test, Mann-Whitney test, Fischer's Exact test, and prevalence ratios with 95% confidence interval. Results. HIV-positive pregnant women had higher proportion of HPV infection than HIV-negative pregnant women (79.5% versus 58.5%; P<.05). HPV positivity prevalence ratio for HIV-positive women was 1.36 (95% CI 1.04-1.8; P=.03). There was significant association between HIV viral load levels and HPV positivity (P<.05). Conclusions. Our results demonstrate higher HPV positivity in HIV-infected pregnant women. Higher values of HIV viral load were associated with HPV positivity.